P3-1-10. Interference effect of personality characteristics on language processing with background music: An event related potential study. Issue 5 (May 2018) - Masaoka, Shiori; Kataoka, Yoshie; Masuda, Megumi; Gunji, Atsuko
Abstract : In an attempt to evaluate the effect of background language reference, we examined the event-related potential (ERP) elicited by reading comprehension while listening to popular song. The subjects were 14 healthy Japanese speakers (21.3 ± 0.8 yrs). ERPs were recorded during judgment of grammatical tenses in English (Et task) or Japanese (Jt task) when exposed to English (Em condition) or Japanese (Jm condition) vocal music. The resultsrevealed a differential pattern of N400 component for native and non-native language processing. Thus, the amplitude of N400 was significantly larger in Et task compared with Jt task regardless of the language of background music (p = .003). Also, the amplitude in Jm condition of Et task showed a positive correlation with the attention deficit hyperactivity disorder (ADHD) index of the subject-rated Conners' Adult ADHD Rating Scales (CAARS) (F3: r = .625, p = .017, F4: r = .584, p = .028). These findings suggest that the non-native language processing with background music is more detrimentally affected by the behavioral characteristics of ADHD.